Landslides and other damage to buildings and infrastructures following the April–May 2015 earthquake sequence, Solukhumbu District, Eastern Nepal (Journal of Nepal Geological Society, 2019)
The study focuses on the eastern margin of the zone affected by the April–May 2015 earthquakes, i.e. the Dudh Koshi River section between the Khari Khola and Monjo (Solukhumbu District). Visits before and after the earthquake sequence allowed us to assess the geomorphic changes caused by the earthquakes and the subsequent monsoon. These changes are characterized by land sliding (rock falls, rockslides, landslides, gullies and debris flows), and cascading processes, which supplied coarse debris into rivers (bed load).The impact of the earthquakes on buildings, trails and existing infrastructures (canals, hydropower plants) was also investigated. While the age and construction quality of buildings are of some import, other parameters such as the nature and depth of colluvial deposits appear to be significant factors likely to amplify the effects of ground shaking, as observed on large block fields south-west of the Khari Khola catchment, which might be inherited from former undated seismic events.